Small, incidental hepatic epithelioid haemangioendothelioma the role of ablative therapy in borderline patients. Issue 8 (20th August 2018) - Kamarajah, Sivesh K; Robinson, Daniel; Littler, Pete; White, Steven A
Abstract: Primary hepatic epithelioid hemangioendothelioma (HEHE) is an extremely rare tumor of vascular origin with an incidence of <0.1 per 100 000 population. We describe a 70-year-old man with renal cell carcinoma managed via robotic right partial nephrectomy who was also found to have a solitary 10 mm lesion on a pre-operative staging computer tomography (CT) scan. The patient underwent percutaneous biopsy and local ablation of the lesion consistent with an epithelioid hepatic haemangioendothelioma. Post-procedure CT scan after 1 month showed adequate ablation margins with no new lesions. The role of local ablation for solitary, small HEHE is discussed.